2010
DOI: 10.1007/s00467-010-1617-8
|View full text |Cite
|
Sign up to set email alerts
|

Similar renal outcomes in children with ADPKD diagnosed by screening or presenting with symptoms

Abstract: Autosomal dominant polycystic kidney disease (ADPKD) in children is sometimes considered to be a benign condition, with morbidity manifesting in adulthood. Therefore, diagnostic screening of children at risk is controversial. The aim of our study was to to compare the manifestations of ADPKD in children diagnosed by postnatal ultrasound (US) screening versus those presenting with symptoms. This was a retrospective chart review of children with ADPKD assessed in a single centre between 1987 and 2007. Age and re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
49
0
2

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 35 publications
(52 citation statements)
references
References 45 publications
1
49
0
2
Order By: Relevance
“…By contrast, children with ten or fewer cysts had a nonsignificantly increased self-reported urinary frequency and no decrease in concentrating ability compared with children of parents with ADPKD who did not have any cysts on ultrasonography. A study that included 16 children who were diagnosed with ADPKD because of their symptoms found that only 1 of these children presented with enuresis 16 ; this frequency is probably similar to that of the general paediatric population. As vasopressin antagonists reduce the rate of cyst growth and eGFR loss in patients with ADPKD 112,113 , vasopressin analogues can reasonably be considered to be detrimental in these patients; therefore, it seems wise to prefer other treatment options for the management of nocturnal enuresis in children with ADPKD 111 .…”
Section: Vasopressin Analoguesmentioning
confidence: 83%
See 1 more Smart Citation
“…By contrast, children with ten or fewer cysts had a nonsignificantly increased self-reported urinary frequency and no decrease in concentrating ability compared with children of parents with ADPKD who did not have any cysts on ultrasonography. A study that included 16 children who were diagnosed with ADPKD because of their symptoms found that only 1 of these children presented with enuresis 16 ; this frequency is probably similar to that of the general paediatric population. As vasopressin antagonists reduce the rate of cyst growth and eGFR loss in patients with ADPKD 112,113 , vasopressin analogues can reasonably be considered to be detrimental in these patients; therefore, it seems wise to prefer other treatment options for the management of nocturnal enuresis in children with ADPKD 111 .…”
Section: Vasopressin Analoguesmentioning
confidence: 83%
“…An important argument against diagnostic testing for ADPKD in childhood is respecting the autonomy of the children or young adults to decide whether to undergo testing for a genetic disease for which a diagnosis might not have therapeutic consequences until adulthood. Treatments to slow disease progression in children with ADPKD are limited, and no clear evidence exists to suggest that presymptomatic detection improves outcomes 16 . In addition, establishing a clinical or genetic diagnosis may have a substantial impact on the future ability of the child to secure insurance policies or to gain access to certain professions.…”
Section: Counsellingmentioning
confidence: 99%
“…Cascade screening, however, is controversial if the screened individual is without symptoms and there is no established therapy to prevent or delay the onset of the disease. An example is autosomal dominant polycystic kidney disease (ADPKD), where establishing the diagnosis in asymptomatic children with a family history of ADPKD may cause stress and anxiety and could impair the child's ability to later obtain insurance [6,7]. For this reason, many clinicians defer diagnostic testing until the child is old enough to make that decision, leading to a situation in which the child may be seen annually for blood pressure and urine checks, but where the potential diagnosis is like the proverbial elephant in the room, namely, it is not mentioned.…”
Section: Precise Genetic Counsellingmentioning
confidence: 99%
“…Moreover, cardiovascular abnormalities are described from a young age onwards, and hypertension is the most frequent complication among ADPKD patients. With an average age at diagnosis of 30 years, hypertension affects 60-75% of young adults and 5-44% of children diagnosed with ADPKD [36][37][38] before any substantial reduction of GFR is detected [13,39].…”
Section: Link Between Autosomal Dominant Polycystic Kidney Disease Ementioning
confidence: 99%